2022
DOI: 10.3390/nu14112331
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemia Fluctuations Improvement in Old-Age Prediabetic Subjects Consuming a Quinoa-Based Diet: A Pilot Study

Abstract: This study aimed to observe if quinoa could produce a benefit on postprandial glycemia that would result in less progression to type 2 diabetes (T2D). A cross-over design pilot clinical study with a nutritional intervention for 8 weeks was performed: 4 weeks on a regular diet (RD) and 4 weeks on a quinoa diet (QD). Nine subjects aged ≥65 years with prediabetes were monitored during the first 4 weeks of RD with daily dietary records and FreeStyle Libre®. Subsequently, participants started the QD, where quinoa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…Additionally, the current study also found that total cholesterol, LDL cholesterol, and systolic and diastolic blood pressure in the quinoa group were lower than before the quinoa dietary intervention, suggesting that in addition to reducing postprandial blood glucose, quinoa has benefits in lipid metabolism and blood pressure for people with impaired glucose tolerance. The current study differs from these two studies ( Abellán Ruiz et al, 2017 ; Díaz-Rizzolo et al, 2022 ). First, the participant number in the current study is more extensive, and the age range is much broader.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Additionally, the current study also found that total cholesterol, LDL cholesterol, and systolic and diastolic blood pressure in the quinoa group were lower than before the quinoa dietary intervention, suggesting that in addition to reducing postprandial blood glucose, quinoa has benefits in lipid metabolism and blood pressure for people with impaired glucose tolerance. The current study differs from these two studies ( Abellán Ruiz et al, 2017 ; Díaz-Rizzolo et al, 2022 ). First, the participant number in the current study is more extensive, and the age range is much broader.…”
Section: Discussioncontrasting
confidence: 80%
“…Compared with other common grains such as wheat, rice and millet, quinoa has lower starch content and higher soluble and insoluble fiber content (Repo-Carrasco-Valencia and Serna, 2011;Lamothe et al, 2015). Previous studies (Abellán Ruiz et al, 2017;Díaz-Rizzolo et al, 2022) have found that a quinoa diet can reduce body weight, body mass index, waist circumference and glycosylated hemoglobin levels in people with impaired glucose tolerance. Additionally, the current study also found that total cholesterol, LDL cholesterol, and systolic and diastolic blood pressure in the quinoa group were lower than before the quinoa dietary intervention, suggesting that in addition to reducing postprandial blood glucose, quinoa has benefits in lipid metabolism and blood pressure for people with impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbohydrate profile of quinoa, with its high-quality starch and dietary fiber, highlights its nutritional value and its ability to support healthy diets and prevent type 2 diabetes. This combination can help manage postprandial glycemia, positioning quinoa as a key functional food [52]. Additionally, quinoa contains a high amount of essential fatty acids, minerals, vitamins, dietary fibers, and carbohydrates, having beneficial hypoglycemic effects while being gluten-free [20].…”
Section: Water Activity and Proximate Compositionmentioning
confidence: 99%